Factors Influencing the Adoption of Clinical Informatics Tools among Medical Doctors in South Africa - Owolabi, Kehinde Aboyami; Nurudeen, Nurudeen Adeniyi; Neil, Evans D (University of Dar es Salaam Library Journal, 2020)
The adoption of clinical informatics tools is not encouraging in many developing countries and a better understanding of the factors that influence their integration is expected to promote their effective utilisation. To shed more light on this phenomenon, the study employed the use of Universal Theory of Acceptance and Use of Technology (UTAUT) to identify the factors that influence the use of clinical informatics tools. The study employed a positivism research paradigm anchored on survey research design. Simple random sampling technique was used to select one hundred and five medical doctors in a tertiary hospital in South Africa. Data were collected with the use of a structured questionnaire. Structural equation modelling was used to analyse the data collected. Findings from the study reveal that effort expectancy was related to behavioural intention to use clinical informatics ( = 0.41, p< 0.05). Also, performance expectancy was related to behavioural intention to use clinical informatics ( = 0.47, p< 0.01). The study therefore recommends that the hospital management should create conducive environment that will promote effective use of clinical informatics tools and organise training programmes for effective use of the tools. The study also sees the need for technology producers to make the tools more user-friendly.